STUDI DAYA TARIK WISATA ALAM HUTAN MANGROVE PANTAI BAROS BANTUL, HUTAN MANGROVE WANA TIRTA PANTAI PASIR KADILANGU, HUTAN MANGROVE JEMBATAN API-API TEMON DAN KINERJA BISNIS PARIWISATA - Hasan, Ali (JURNAL MEDIA WISATA: Wahana Informasi Pariwisata, 2018)
The purpose of this study is to explain the influence of natural tourist attraction (attractions, aminity, accessibility) on the performance of nature-based tourism businesses. The unit of analysis of this study was 207 tourists visiting to Hutan Mangrove Pantai Baros Bantul, Hutan Mangrove Wana Tirta, Pantai Pasir Kadilangu, dan Hutan Mangrove Jembatan Api-Api Temon Kulonprogo taken by incidental sampling technique. the data was collected by a questionnaire validated with pathwhole and cronbach alpha. Normality and multicollinearity tests were used to test the feasibility of variables as a condition for the use of partial regression analysis. The findings of this study show the long-term impact of satisfaction and a significant revisit on the absorption of labor and income of local communities as an important of the business performance of the nature-based tourism. Keywords: Nature tourism attractions, attractions, amenities, accessibility, satisfaction, repeat visits and tourism business performance.